New species of Rhodobaenus LeConte, 1876 (Coleoptera: Curculionidae: Dryophthorinae) from Central and South America - Anderson, Robert S. (Zootaxa, 2022)
Four new species of Central and South American Rhodobaenus LeConte (Coleoptera: Curculionidae: Dryophthorinae) are described: R. chamorroae Anderson, new species (type locality Colombia, Valle del Cauca), R. flecha Anderson, new species (type locality Costa Rica, Cartago), R. howdenorum Anderson, new species (type locality Ecuador, Rio Palenque), and Rhodobaenus schusteri Anderson, new species (type locality Guatemala, Zacapa). Diagnostic characters and images are provided for all new species to facilitate identification. The previously unknown male of Rhodobaenus tenorio Anderson is here described, and the species, previously only known from Costa Rica, is here recorded from Guatemala.